Cross validation of the Multiple Electrode Aggregometry - Siller-Matula, Jolanta M.; Gouya, Ghazaleh; Wolzt, Michael; Jilma, Bernd (Thrombosis and Haemostasis, 2009)
Several test systems exist for assessment of platelet function in patients under clopidogrel or aspirin therapy. The objective was to cross-validate the Multiple Electrode Aggregometry (MEA) with three other methods used for determining platelet reactivity under treatment with clopidogrel and aspirin. Platelet function was assessed by the MEA, Vasodilator Stimulated Phosphoprotein (VASP) phosphorylation assay, Platelet Function Analyzer-100 (PFA-100) and the Cone and Platelet Analyzer. Measurements were performed in blood from nine healthy volunteers at baseline, 2, 4, 6 and 72 hours after clopidogrel and aspirin loading. The apparent effect size for clopidogrel and aspirin was greatest for the MEA: treatment induced a 19-fold difference in the arachidonic acid-induced platelet aggregation and an 11-fold difference in the adenosine diphosphate-induced platelet aggregation before/after treatment. For comparison, aspirin and clopidogrel induced only 2.0– to 2.6 -fold changes in other tests (VASP assay, Cone and Platelet Analyzer and PFA-100). Maximal effects were seen 2 hours after aspirin loading and shorter than 72 hours after clopidogrel loading. In conclusion, aspirin and clopidogrel produce stronger signals in the MEA compared to several other methods.
Keywords: Antiplatelet; aspirin; clopidogrel; platelet function; Multiplate Analyzer